ANALISIS PEMANFAATAN SARANA DAN PRASARANA OLAHRAGA DI LINGKUNGAN SEKOLAH DALAM MENDUKUNG AKTIVITAS FISIK SISWA - Andi Sri Rafiqa Hayu; Fatmasari; Adnan Annur; Muh. Yunus; Muh. Akbar Al Farisi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to analyze the utilization of sports facilities and infrastructure in the school environment to support students' physical activities. The study employed a quantitative approach using a descriptive research design. The participants consisted of students who were directly involved in physical education learning and sports activities at school. Data were collected through observation, questionnaires, and documentation. The collected data were analyzed using descriptive statistical techniques, including percentages and mean scores, to describe the level of utilization of sports facilities and infrastructure. The findings revealed that the sports facilities and infrastructure available at the school were generally categorized as adequate and had been optimally utilized in Physical Education, Sports, and Health (PJOK) learning activities as well as extracurricular programs. The utilization of these facilities positively influenced students' participation, motivation, and physical activities. However, several challenges were identified, including the limited number of sports equipment and the need for regular maintenance to maximize their use. Therefore, continuous management and development of sports facilities and infrastructure are necessary to create a healthy, active, and conducive school environment that supports students' overall development.